2017
DOI: 10.1021/acs.jafc.7b00805
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin Inhibits β-Amyloid Assembly and Attenuates β-Amyloid Oligomer-Induced Cognitive Impairments

Abstract: β-Amyloid (Aβ) can form aggregates through self-assembly and produce neurotoxicity in the early stage of Alzheimer's disease (AD). Therefore, the inhibition of Aβ assembly is considered as the primary target for AD therapy. In this study, we reported that fucoxanthin, a marine carotenoid, potently reduced the formation of Aβ fibrils and oligomers. Moreover, the fucoxanthin-triggered modification significantly reduced the neurotoxicity of Aβ oligomers in vitro. Molecular dynamics simulation analysis further rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 44 publications
6
116
1
Order By: Relevance
“…In fact, fucoxanthin showed significant neuroprotection to PC-12 cells against Aβ 1-42 at all tested concentrations (0.01-2 µM) in this study (p<0.05). These results are comparable to recent studies as 1 µM of fucoxanthin demonstrated the ability to increase cell viability compromised by Aβ 1-42 in SH-SY5Y cells from 50% to almost 80% (Xiang et al, 2017), and increase cell viability from 55% to 87% comparing to control Aβ oligomer-induced toxicity in SH-SY5Y cells (Lin et al, 2017). In our study 1 µM of fucoxanthin was able to increase cell viability compromised by Aβ 1-42 from around 67% to 98.5% in PC12 cells.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
See 2 more Smart Citations
“…In fact, fucoxanthin showed significant neuroprotection to PC-12 cells against Aβ 1-42 at all tested concentrations (0.01-2 µM) in this study (p<0.05). These results are comparable to recent studies as 1 µM of fucoxanthin demonstrated the ability to increase cell viability compromised by Aβ 1-42 in SH-SY5Y cells from 50% to almost 80% (Xiang et al, 2017), and increase cell viability from 55% to 87% comparing to control Aβ oligomer-induced toxicity in SH-SY5Y cells (Lin et al, 2017). In our study 1 µM of fucoxanthin was able to increase cell viability compromised by Aβ 1-42 from around 67% to 98.5% in PC12 cells.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…The strongest activity was at 10 µM, but this concentration was toxic to PC-12 cells. Earlier research demonstrated that fucoxanthin at more than 1 µM was able to reduce 50% of Aβ 1-42 aggregation (Xiang et al, 2017), while in this study 1 µM of fucoxanthin was able to reduce more than 50% of Aβ 1-42 aggregation.…”
Section: Accepted Manuscriptcontrasting
confidence: 53%
See 1 more Smart Citation
“…For example, fucoxanthin treatment reduced Aβ-induced damage in a cultured cell model through several mechanisms including downregulation of apoptotic factors, inhibition of inflammatory cytokine-mediating action, and simultaneous reduction of ROS [70]. High levels of carotenoids within the brain, such as lutein and zeaxanthin, can enhance cognitive function in elderly people, exerting neuroprotection with a reduction of neuronal mortality [71].…”
Section: Brain Processes Involved In Neurodegeneration and Protectmentioning
confidence: 99%
“…Preparation of Aβ 1-42 oligomer. Soluble Aβ 1-42 oligomer was obtained as previously described (23). Briefly, Aβ 1-42 (GL Biochem) was added in hexafluoroisopropanol (HFIP) to form the Aβ 1-42 monomer, which was further spin-vacuumed in 10% HFIP solution.…”
Section: Measurement Of Ache Activitymentioning
confidence: 99%